Dynamic Psychotherapy as a PTSD Treatment for Firefighters: A Case Study - Becker, Joana Proença (2022)
In Portugal, forest fires are responsible for disasters that tend to be repeated annually, leading to dramatic consequences, such as those that have occurred in 2017, with the destruction of hundreds of houses and the deaths of dozens of people. Firefighters who are exposed to these potentially traumatic events are considered a high-risk group for the development of stress-related disorders. The aim of this study was to monitor the progress of two firefighters with symptoms of post-traumatic stress disorder (PTSD) treated through dynamic psychotherapy (DP) and to assess the feasibility of implementing this intervention within fire departments. A female firefighter and a male firefighter, with similar sociodemographic characteristics and PTSD symptom severity, were selected to verify the treatment applicability for both genders. The symptomatology changes were assessed through a set of instruments (PHQ-15, PCL-5, BSI, DASS, and CALPAS-P) applied every three months over 15 months (including pre-treatment, treatment period, and post-treatment). DP seemed to be an effective treatment for PTSD symptoms, with patients showing a state of increasing improvement even after the end of treatment. The acceptability to firefighters, the treatment adherence, the therapeutic alliance, and the reduction in PTSD symptoms suggest feasibility for implementing this intervention inside the Portuguese fire departments.